Memaknai Akun Media Sosial Satire Kristen dalam Perspektif Etis-Teologis - Olimbovo, Senopati Salomo; Novalina, Martina (Jurnal EFATA: Jurnal Teologi dan Pelayanan, 2023)
This research is motivated by several irregularities that often occur in the church. This problem results in harmony in the church; for example, the relationship between the congregation and the Pastor becomes tenuous due to irregular teaching. Satire is valuable to satirize someone so that the person being ridiculed makes improvements and thinks more broadly. You can often find satirical sentences on social media accounts, both satire and sarcasm. But this time, many social media accounts are displaying satirical language-style forms of satire about the church, both in terms of order and teachings in the church. This article raises issues that exist on the social media account @gerejapalsu. This account can be a consideration regarding Pastors who are considered to emphasize their physical appearance rather than the truth of the Word that will be conveyed and teachings that are "considered" wrong by the account manager. This research aims to examine this phenomenon from an ethical and theological perspective so that the congregation can consider the positive side of the topic raised by the social media account @gerejapalsu. The method used in the article is a qualitative approach, and the study is in descriptive form using the literature study method. The results of the study show that the existence of this Christian satirical account has a good and functional purpose. Having a party that oversees the church and God's servants will minimize the possibility of damage to the church system. In addition, this phenomenon is helpful as a driving force or trigger for the congregation to think critically and be sensitive to existing problems. Abstrak Di akun media sosial seringkali ditemukan kalimat sindiran baik bersifat satire maupun sarkasme. Namun kali ini, banyak akun media sosial yang menampilkan bentuk sindiran bergaya bahasa satire mengenai gereja, baik secara tatanan maupun ajaran-ajaran dalam gereja. Artikel ini mengangkat permasalahan yang ada di akun media sosial @gerejapalsu. Tujuan dari penelitian ini adalah mengkaji fenomena ini dari kacamata etika dan teologis agar jemaat mampu mempertimbangkan sisi positif dari topik yang diangkat oleh akun media sosial @gerejapalsu. Pendekatan yang digunakan dalam artikel adalah pendekatan kualitatif serta kajian dalam bentuk deskriptif dengan metode studi pustaka. Hasil penelitian menunjukan bahwa keberadaan akun satire Kristen ini sebenarnya memiliki tujuan yang baik dan bermanfaat. Dengan adanya pihak yang mengawasi gereja dan para pelayan gereja akan mengecilkan kemungkinan terjadinya kerusakan di dalam sistem gereja. Selain itu fenomena ini berguna sebagai pendorong atau pemicu jemaat untuk mampu berfikir secara kritis dan peka terhadap permasa-lahan yang ada.